THE CONTRIBUTION OF CLUSTERING TECHNIQUE IN DEVELOPING IDEAS ON A SHORT PARAGRAPH FOR THE FIRST YEAR ENGLISH EDUCATION STUDENTS OF STAI MIFTAHUL ULUM TANJUNGPINANG - Eka Mayasari (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2018)
In writing students usually difficult in developing and expressing their ideas, they have not various sentences in writing a paragraph; they also sometimes confuse to start to make their paragraph pursuant to the topic of which given from teacher. This matter which make blase and student bored in writing. Hence from that, the researcher used a clustering technique to assist students in developing and expressing their paragraph, and help the students more variety in writing a paragraph. So that their interesting and nattier paragraph, directional and also its development pursuant to the topic of which given from the lecturer. This research is an experimental research. There was two variable of the research; there were independent and dependent variables. In conducting the data collection, the researcher conducted treatment in teaching writing in students’ developing ideas using clustering technique. The researcher gave pre-test and post-test to the students. The students write a hortatory exposition text in 45 minutes without clustering for control and the students write a hortatory exposition text in 45 minutes through clustering for the experimental group. As the result, students who are taught through clustering have different in developing ideas from those who are taught without clustering. Furthermore, it can be said that there was a significant contribution to the students’ developing ideas after using a clustering technique for the first year English student at STAI miftahul ‘Ulum Tanjungpinang.